2019
DOI: 10.1001/jamaoto.2019.1012
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Head and Neck Cancer in Patients With Prior Hematologic Malignant Tumors

Abstract: IMPORTANCE More than 1.3 million people in the United States have a hematologic malignant tumor currently or in remission. Previous studies have demonstrated an increased risk of secondary neoplasms in patients with hematologic malignant tumors, but research specifically on the risk of head and neck solid tumors in patients with prior hematologic malignant tumors is limited. OBJECTIVES To examine a possible association between prior hematologic malignant tumors and risk of head and neck cancer and to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…These patients are overdiagnosed, which caused 90% of new cases in South Korea, 70% in the United States, Italy, France and Australia, and about 50% in Japan and England (24). The evidence supporting the overdiagnosis hypothesis includes: (1) The increase in the incidence of TC is accompanied by a stable or decreasing death rate (16,25,26); (2) The detection of small-sized tumors increased (27,28); (3) The number of new cases of TC is closely related to the number of examinations by ultrasound, CT and other diagnostic techniques (29, 30). However, there are also evidences that challenge the view of overdiagnosis: (1) The detection of large tumors is also increasing, not only small tumors (31,32); (2) Although the overall death rate remained stable, the mortality of advanced tumors really increased (33,34); (3) Molecular genetic characteristics of TC such as BRAF and RAS mutations are changing with time (35).…”
Section: The Period Effectmentioning
confidence: 99%
“…These patients are overdiagnosed, which caused 90% of new cases in South Korea, 70% in the United States, Italy, France and Australia, and about 50% in Japan and England (24). The evidence supporting the overdiagnosis hypothesis includes: (1) The increase in the incidence of TC is accompanied by a stable or decreasing death rate (16,25,26); (2) The detection of small-sized tumors increased (27,28); (3) The number of new cases of TC is closely related to the number of examinations by ultrasound, CT and other diagnostic techniques (29, 30). However, there are also evidences that challenge the view of overdiagnosis: (1) The detection of large tumors is also increasing, not only small tumors (31,32); (2) Although the overall death rate remained stable, the mortality of advanced tumors really increased (33,34); (3) Molecular genetic characteristics of TC such as BRAF and RAS mutations are changing with time (35).…”
Section: The Period Effectmentioning
confidence: 99%
“…In addition, studies have shown that TKI-treated CML patients have an increased risk of developing secondary malignancies with a predisposition to specific organs, including the head and neck, cervix, and prostate [7][8][9]. Moreover, a retrospective analysis using the Veterans Affairs (VA) Corporate Data Warehouse (CDW) suggested that prior HM was negatively associated with survival among patients with second primary head and neck squamous cell carcinoma (SCC) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the immune system in tumor regulation is particularly evident in the immunocompromised. Iatrogenic solid organ transplant, diabetes, autoimmunity requiring immunosuppressive therapy, HIV and hemoproliferative malignant disease or disorders and aging, are all associated with an increased risk of developing head and neck cancer (HNC) and worse outcomes [1][2][3][4][5][6][7][8][9][10][11]. Proliferating tumors utilize many forms of immunosuppression to tip the balance of immunoediting toward tumor progression [12].…”
Section: Introductionmentioning
confidence: 99%